THE RANGE OF SPINEL COMPOSITIONS IN TERRESTRIAL MAFIC AND ULTRAMAFIC ROCKS - Barnes S.J.; Roeder P.L. (My University, 2001)
Compositional fields for spinels from a wide variety of maficultramafic igneous rock types and tectonic environments have been determined from a global database of over 26 000 analyses. These fields are defined using contoured data density plots based on the spinel prism, and plots of TiO2 us ferric iron, for mantle xenoliths, ophiolitic rocks, continental layered instrusions, alkalic and lamprophyric rocks, tholeiitic basalts, Alaskan ultramafic complexes and komatiites. Several trends appear regularly in the various environments: a trend of widely variable Cr/(Cr + Al) at low Fe2+/(Mg + Fe2+) (the Cr-Al trend); increasing Fe3+, Fe2+/ (Mg +Fe2+) and TiO2 at constant Cr/(Cr + Al) (Fe-Ti trend); a trend found primarily in kimberlites, similar to Fe-Ti but at constant Fe2+/ (Mg + Fe2+); and an unusual trend of increasing Al found only in layered intrusions. The Cr-Al and Fe-Ti trends are both found to varying degrees in tholeiitic basalts. The Cr-Al trend is prevalent in rocks that have equilibrated over a range of pressures, whereas the Fe-Ti trend is dominantly due to low-pressure fractionation. The most Cr-rich chromites found in nature occur in boninites, diamond-bearing kimberlites, some komatiites and ophiolitic chromitites. Exceptionally reduced chromites are found in some komatiites and in ophiolitic chromitites. Detrital chromites from the Witwatersrand conglomerates are of komatiitic provenance.
Keywords: basalt; chromite; kimberlite; ophiolite; spinel